2024
DOI: 10.1371/journal.pone.0293895
|View full text |Cite
|
Sign up to set email alerts
|

Falcon gut microbiota is shaped by diet and enriched in Salmonella

Anique R. Ahmad,
Samuel Ridgeway,
Ahmed A. Shibl
et al.

Abstract: The gut microbiome is increasingly being appreciated as a master regulator of animal health. However, avian gut microbiome studies commonly focus on birds of economic importance and the gut microbiomes of raptors remain underexplored. Here we examine the gut microbiota of 29 captive falcons—raptors of historic importance—in the context of avian evolution by sequencing the V4 region of the 16S rRNA gene. Our results reveal that evolutionary histories and diet are significantly associated with avian gut microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 78 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…This change can already occur after a month of direct contact between animals and humans, and the diet, especially if based on raw food, represents the first determining causal factor [ 39 , 40 , 41 ]. Some studies have shown that birds of prey fed poultry meat develop a wider range of Gram-negative bacterial flora [ 38 ]; in particular, a study on falcons has shown that the diets most commonly fed to these birds increase the levels of Salmonella in the intestinal flora [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This change can already occur after a month of direct contact between animals and humans, and the diet, especially if based on raw food, represents the first determining causal factor [ 39 , 40 , 41 ]. Some studies have shown that birds of prey fed poultry meat develop a wider range of Gram-negative bacterial flora [ 38 ]; in particular, a study on falcons has shown that the diets most commonly fed to these birds increase the levels of Salmonella in the intestinal flora [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Captivity is presently known to affect gut and oral microbiome diversity in birds of prey when compared to their wild counterparts, with observable changes within just one month of direct human contact, and diet is being pointed to as the main factor responsible for alterations in the oral microbiome [ 60 , 61 , 62 , 63 , 64 , 65 ]. For example, studies have shown that birds who are fed chicken are linked to a wider diversity of Gram-negative bacteria [ 66 ], and that the diet commonly provided to captive animals increases the levels of Salmonella in falcons [ 65 ]. Some other factors responsible for altering the microbiome in birds of prey are also shown in Figure 1 .…”
Section: Bacteria Found In Captive Birds Of Preymentioning
confidence: 99%
“… Some variables suspected to alter the microbiome of birds of prey in captivity: contact with wildlife; direct contact with human and animal waste; contact with synanthropic species; contact with domestic waterfowl; contact with other pet birds; diet; and previous exposure to antibiotics. Based on [ 25 , 27 , 32 , 33 , 34 , 35 , 36 , 60 , 61 , 62 , 63 , 64 , 65 ] and created using BioRender ( ). …”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations